Penerapan Model Pembelajaran Kooperatif Tipe Jigsaw Terhadap Peningkatan Kemampuan Berpikir Kritis pada Konsep Pencemaran Lingkungan di SMA Negeri 12 Banda Aceh - Almukarram Almukarram; Muhammad Ali Sarong; Evi Apriana (Universitas Islam Negeri Ar-Raniry, 2016)
This study aims to determine differences in the students' critical thinking skills through the application of cooperative learning jigsaw with conventional learning the concepts of environmental pollution in SMA 12 Banda Aceh. Data were collected in April 2016. The method used in this study was an experimental method with pretest posttest control design. The research was conducted in two classes, namely X-IPA 1 as the experimental class and X-IPA 2 as the control class. The instrument used in this study using multiple choice questions to assess students' critical thinking. Data analysis used independent sample t-test with SPSS 16.0 for Windows at significant level of 0.05. T test results showed tvalue>t table was to think critically 6.633> 2.68. The conclusions show that there are differences in critical thinking ability of students to use the application model of cooperative learning jigsaw with the conventional concept of environmental pollution in SMA 12 Banda Aceh.